Developing and piloting a serious game to educate children about over-the-counter medication safety. Issue 2 (21st February 2019) - Abraham, Olufunmilola; Feathers, Alison; Grieve, Lorin; Babichenko, Dmitriy
Abstract: Objective: Misuse of over-the-counter (OTC) medications among children is a growing public health and medication safety problem. Serious games are increasingly being used to foster healthy self-management behaviours and decision-making among children. We developed and pilot-tested using a serious game to educate children about OTC medication safety. Methods: Students (aged 15–17) at a public school serving grades 6–12 in Western Pennsylvania were recruited to play the game. Open-ended questions were asked following gameplay to obtain participants' feedback about ease of play and additional changes that would be needed to improve the game. Gameplay was video recorded using a screen recording software to observe participants' behaviours while playing the game. Participants OTC medication safety knowledge was assessed before and after gameplay using pre/post questionnaires. Key findings: All the participants liked the game, reporting that it was easy to navigate and fun to play. Gameplay screen recordings revealed at least three areas that would need to be redesigned for the game to be more engaging and effective. Seven out of the nine participants (78%) changed their answer to at least one question on the OTC medication safety post-test survey compared to their pre-test answers. There was an increase in the percentage of correct answers in the post-test survey for questions asking about correct dosing and active ingredients. Three responses remained unchanged and the percentage of correct answers for the post-test survey decreased for questions about the drug facts label and side effects. Conclusion: This pilot suggests that a serious game may influence participants' knowledge and attitude about OTC medication safety. Further research is needed to examine the potential of using serious games to teach children about safe medication use and negative consequences of inappropriate use.